Preference for High Dietary Salt Intake Is Associated With Undiagnosed Type 2 Diabetes: The Henan Rural Cohort - Abdulai, Tanko; Runqi, Tu; Mao, Zhenxing; Oppong, Timothy Bonney; Amponsem-Boateng, Cecilia; Wang, Yan; Liu, Xiaotian; Zhang, Haiqing; Wang, Chongjian (Frontiers in Nutrition, 2020)
Background: Diabetes continues to be a serious disease burden globally. Nutrition plays a vital role in human life and health, and both inadequate and over nutrition have been implicated in cause the of disease. Objective: We explored the role of preference for high dietary salt intake and diabetes in a rural population. We also looked at possible mediating factors in the relationship between diabetes and preference for high dietary salt intake. Methods/Participants: Data from the Henan rural cohort in China were analyzed. Using multinomial regression models, the association between diabetes diagnosis type and reported preference for dietary salt was assessed. Adjusted odds ratios (aORs) with confidence interval (CI) at a 95% level are reported. Mediation analyses using structural equation models in Stata were performed. Results: Of the 39,183 participants included in the analyses, 4.07% were previously diagnosed with diabetes, and 5.80% with undiagnosed diabetes. Eighteen percent had a preference for salty meals, the mean age was 55.45 years, and 60% were women. Preference for salty meals was associated with undiagnosed diabetes (aOR = 1.17, 95% CI 1.03, 1.32), but not with previously diagnosed diabetes. Stratified analysis revealed that the association with undiagnosed diabetes was only significant in men (aOR = 1.36, 95% CI 1.13, 1.70) but not in women (aOR = 1.06, 95% CI 0.81, 1.38). BMI and central obesity fully mediated the association. Dietary salt intake was self-reported and therefore presents a limitation. Conclusion: Our study demonstrated that preference for high dietary salt intake is associated with undiagnosed diabetes but not prevalent diabetes.